Distribution of Lung Cancer Patients in Dharmais Cancer Hospital Year 2008-2012 - Fariha Ramadhaniah; Desy Khairina; Dian Triana Sinulingga; Evlina Suzanna; Achmad Mulawarman Jayusman (Jurnal Respirologi Indonesia, 2019)
Background: Lung cancer is the most commonly found cancer. At the population level, the incidence and mortality from lung cancer ranks first among all cancer cases which occur in male and the fourth most common cancer in female, while the survival of lung cancer is very short, namely 13 months. This study describes several variables of lung cancer cases at the Dharmais Cancer Hospital epidemiologically and clinically. Methods: The study was a cross-sectional study using the lung cancer data from 2008-2012 in Dharmais Cancer Hospital with hospital-based cancer registration data sources. Results: Cases of lung cancer in male are three times more common when compared to female and cases begin to increase in the 45-year age group. The location of the tumor was more commonly found in the right lung (48.2%) and adenocarcinoma was the most common type found (41,7%). The cancer stage at the time of the first hospital visit was mostly unknown (60.1%) and bone is the most commonly found (36,4%) metastasis location. Conclusion: The lung cancer location in the right lung, adenocarcinoma type, stage unknown in the first hospital visit and bone metastasis was the most commonly found epidemiology and clinical lung cancer patients in Dharmais Cancer Hospital. (J Respir Indo 2019; 39(1): 31-6)